The Debtor: A Novel - Freeman, Mary Eleanor Wilkins, 1852-1930; Stevens, William Dodge, 1870-1942 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Debtor: A Novel" by Mary E. Wilkins Freeman is a work of fiction written in the early 20th century. The story is set in the small village of Banbridge, which is influenced by the wealth and activity of the nearby city. It focuses on the lives of its residents, particularly the socially conscious women who navigate the complexities of propriety and class, setting the stage for themes of social class, wealth, and human interaction. At the start of the novel, we are introduced to Banbridge, a village where societal norms dictate behavior and social interactions. The opening chapter follows Mrs. Henry Lee and Mrs. William Van Dorn as they navigate a spring afternoon of making fashionable social calls in a private coach. Their visit leads to awkward encounters and a significantly humorous mishap when they discover that the new residents, the Carrolls, are not at home and have left their door ajar. The scene is filled with rich descriptions of the characters, the village life, and the tensions between social expectations and human behavior, hinting at deeper themes of aspiration, societal norms, and the traps of curiosity that will unfold throughout the narrative. (This is an automatically generated summary.)
Release date is 2006-02-19
Produced by Jeff Kaylin and Andrew Sly
Keywords: New Jersey -- Social life and customs -- Fiction